The women [large type] - Hannah, Kristin (Center Point Large Print, 2024)
"'Women can be heroes, too.' When twenty-year-old nursing student Frances Frankie McGrath hears these unexpected words, it is a revelation. Raised on idyllic Coronado Island and sheltered by her conservative parents, she has always prided herself on doing the right thing, being a good girl. But in 1965 the world is changing, and she suddenly imagines a different choice for her life. When her brother ships out to serve in Vietnam, she impulsively joins the Army Nurse Corps and follows his path. As green and inexperienced as the men sent to Vietnam to fight, Frankie is overwhelmed by the chaos and destruction of war, as well as the unexpected trauma of coming home to a changed and politically divided America. The Women is the story of one woman gone to war, but it shines a light on the story of all women who put themselves in harm's way to help others. Women whose sacrifice and commitment to their country has all too often been forgotten."--